EXAMINING EFFECT OF EXAMS STRESS ON STUDENTS’ PERSONALITY TRAITS. AZERBAIJAN CASE - Vusala Karam Musayeva; Shahinzade Gunel Ogtay; Hajiyeva Ilahe Dilkhosh (International Journal of Innovative Technologies in Social Science, 2025)
The exam, and quiz assessment is one of the part of modern educational system. This assessment effect academic results of the students, and also their emotional state. These factors can be observed in their personality traits, too. This research devoted to study the students’ personality traits before and after the exams. The present study examines the students’ personality traits, and their emotional states. The methodology of the study was developed based on constructivist approach, and the main tool of the research - survey questions assess the personality traits. The study was realized at Faculty of Social science and psychology, Baku State University in 2025. The results, and relation between dependent and independent variables were analyzed using SPSS program. The verification of the research questions reveals statistically significant positive results. These findings enable us to assume that the exam stress can decrease the students’ effective communication skills, their interpersonal relationships, self-esteem, and self-regulation abilities. The obtained results can be taken into account in developing training programs to increase the coping strategies of the students at the university community.